The effect of milling parameters on extraction yield of asiaticoside and asiatic acid from centella asiatica nanopowders / Muhammad Zuhairi Borhan - Borhan, Muhammad Zuhairi (2014)
Centella asiatica nanopowders were produced using planetary ball mill. Parametric studies were done to determine the optimum parameters to produce smaller particles size (nanometer) and at the same time yield the highest extraction yield of asiatic acid. The milling parameters includes the effect of bead size (2 and 4 mm, in diameter), effect of mass concentration (0.4-2.8 w/v, %) effect of milling time (2-8 hours) and lastly effect of bead amount (5-100g). The size reduction was carried out in a wet mill with a fixed amount of solvent of 25 ml for each milling set and ultrapure water was used as a milling solvent. The Centella asiatica nanopowders were then analysed using several analytical techniques which are Spectroscopy (Pf.S), Field Emission scanning electron microscope (FESEM) and high performance liquid chromatography (HPLC).Based on the inspection of the Centella asiatica particles size and extraction yield of asiatic acid, it was found that the following parameters can be considered as the optimized parameter to produce higher quality of Centella asiatica nanopowders; the bead size and amount; 2mm and 25g, milling at 4 hours and produced at 1.2 (w/v,%) mass concentration where the size of particles ground at this condition is 283 nm in average and extraction yield of asiatic acid with 25mg/g. The morphology of nanopowders shows that the particles exist in agglomerated particles with size of grain below 1 urn, In this study, possible extraction mechanism is also establish to show difference from microparticles. The properties that contribute to the improved extraction yield of asiatic acid using nanopowders also were explained. The heavy metal analysis was also carried out on the nanopowders. The results were compared with micropowders because the heavy metal contamination is a seriously concern in herbal powder preparation. Results show nanopowders contain higher heavy metal content. However, the concentrations of heavy metals are still in the permissible range. Last but not least, this study also investigated the water extraction yield of asiatic acid between nanopowders and micropowders that shows the elevation of asiatic acid content in the water extract. In a nutshell, it can be concluded that the production of nanopowders can improve extraction yield of active compound and may revolutionize the sample preparation of herbal medicine in a future.